IMPROVING STUDENTS’ SPEAKING ABILITY BY USING PICTURE - Fitri Julianti (Journal of English Education Program (JEEP), 2015)
This study examines about students’ speaking ability by using picture in SLB (school with special  need education) Al-Ihsan in Sindangsari Ciamis. The writer chose the topic because she wanted to know whether using the picture is effective to improve students’ speaking ability in SLB (school with special need education) Al-Ihsan in Sindangsari Ciamis. Luoma (2003, p.4) stated that, “speaking as interaction, and speaking as a social and situation-based activity”. Speaking is very important in daily activity, especially in formal education for giving and receiving many knowledge and information. In previously, She find out that picture can improve students’ speaking ability in formal school especially in elementary school, Junior high school, etc. Therefore, she want to teach speaking by using picture to the students in SLB that have disablity. The main problem in this study was whether there is a significant difference in speaking ability between students who are taught by means of picture in SLB (school with special need education) and those who are not. The study employed a qualitative research design, a case study study as a method to investigate the problem. The population in this study was all of students at eighth grade of SLB Al-Ihsan in Sindangsari Ciamis consisting of eight students. The instruments used to collect the data were observation in the form of speaking test. The test itself is a speaking test in the question and answer form of three questions. In conclusion, using picture is effective to improve students’ speaking ability in SLB (school with special need education) Al-Ihsan Sindangsari Cikoneng Ciamis.Key words: Speaking, picture, and special need